Rheological characterization of the thermal gelation of cowpea protein isolates: Effect of pretreatments with high hydrostatic pressure or calcium addition - Peyrano, Felicitas (2019)
Pretreatments with high hydrostatic pressure (HHP) or calcium addition were assessed for thermal gelation of two cowpea protein isolates (protein extraction at pHs 8.0, standard (A8) or 10.0, pH-shifting-modified (A10). Maximum temperature of thermal processing and protein concentration (PC) on rheological behavior during and after gelling process were evaluated for pretreated isolates. The main effects of pretreatments occurred during heating since the proportion of heat-induced interactions that stabilized the matrixes increased. Those effects were due to partial denaturation (induced by HHP) and increase in Td (induced by CaCl2). HHP allowed gelation at temperatures (50–70 °C) lower than denaturation temperature and the obtaining of stronger gels at the highest PC (10.5 or 12.0 g/100 g). Calcium addition allowed gelation at low PC, but higher temperatures (80–95 °C) were required. Despite both pretreatments, A10 retained its ability to gel at lower PC than A8. Pressurized A10-gels were stronger than A8-gels. Calcium-added A10-gels were stronger than A8-gels at low PC (up to 7.5 g/100 g) or at high temperatures (90–95 °C), but no differences were found at high PC or at low temperatures. Thus, calcium-addition canceled those differences between A8 and A10 at high PC and at low temperatures.